Analisis Kedudukan Adat dalam Hukum Waris Islam dan Hindu Beserta Implikasinya - Zakiyatul Ulya (AL-HUKAMA, 2019)
Tradition/’urf is recognized by Islamic law as a legal basis with several conditions. While the use of tradition in the distribution of inheritance is not justified because it is contrary to the provisions of Islamic inheritance which are qat‘iyah al-dilalah and qat‘iyah al-wurud. The distribution based on tradition that can be done with the agreement of the heirs, after knowing their respective parts and no one is harmed, as in article 183 of KHI. Tradition in Hindu is recognized as a source of law, which becomes law and also applies as a law with conditions that are appropriate with atmavan. The position of tradition in inheritance law has been recognized and legalized its enforcement in an area, varna, company or village based on Sloka 40 parts 60 chapter 7, Artas#astra book. Both Islamic and Hindu laws create tradition as the basis for law enforcement. The use of tradition in the distribution of inheritance is not justified by Islam because of it contradicts with Syara’ argument. However, the distribution based on tradition can be done with the agreement of the heirs, according to article 183 of KHI. In contrast, Hindu law legalizes customary enforcement in an area, varna, company or village as inheritance law based on Sloka 40 parts 60 chapter 7, Artas#astra book.